Always a Catch! : how I punched my way into marrying a prince, 1 - Momoyo, Mayo; Mito, Itsuki (Always a Catch!, 2024)
"Maria, the daughter of a duke, grew up believing she would one day inherit her father's dukedom. Accordingly, she focused her attentions on honing her martial arts prowess, while thoughts of marriage fell by the wayside. But the arrival of a baby brother in her family means she's losing her role as heir! Now that she's decided it's time to marry after all, she's arrived a little late to the game! Are there even any eligible bachelors left?"--Back cover.